Principles of Terrestrial Ecosystem Ecology - Chapin, F. Stuart; Matson, Pamela A.; Vitousek, Peter M. (Springer, 2011)
Human activities are affecting the global environment in many ways, with numerous direct and indirect effects on ecosystems. The climate and atmospheric composition of Earth are changing rapidly. Humans have directly modified half of the ice-free terrestrial surface and use 40% of terrestrial production. Our actions are causing the sixth major extinction event in the history of life on Earth and radically modify the interactions among forests, fields, streams, and oceans. This book is written to provide a conceptual basis for understanding terrestrial ecosystem processes and their sensitivity to environmental and biotic changes. We believe that an understanding of ecosystem dynamics must underlie our analysis of both the consequences and the mitigation of human-induced changes. This book is intended to introduce the science of terrestrial ecosystem ecology to advanced undergraduate students, beginning graduate students, and practicing scientists from a wide array of disciplines. We define terrestrial ecosystem ecology to include freshwater ecosystems and their terrestrial matrix. We also include a description of marine ecosystems to provide a broader context for understanding terrestrial ecosystems and as a basis for Earth-System analysis. We provide access to some of the rapidly expanding literature in the many disciplines that contribute to ecosystem understanding. This second edition incorporates new material that accounts for both the substantial scientific advances in ecosystem ecology during the past decade, as well as the evolution of our own understanding.
Keywords: Ecosystem; Ecology